PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS DAN KINERJA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2014-2017) - Rika Novi Krisdayanti; Mohammad Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe aim of this research is to discover the effect of good corporate governance on profitability and stock performance of banking companies that listed on the Indonesian Stock Exchange (IDX). The management also requires financial information contained in financial report which as important tools used by the user to depicts the condition and performance of the company.               The method used in this research is simple Linear Regression. The population in this research is banking companies that listed on the Stock Exchange in 2014 - 2017. The samples were taken comprised of 28 banking companies that had fulfilled the criteria. The analysis used in this research is descriptive statistical analysis, normality test, model test (F test), and statistical test t. The result of this study showed that Good Corporate Governance has a positive effect significantly on the Profitability that uses the Return on Assets (ROA), Return on Equity (ROE), and also the Net Interest Margin (NIM). And Good Corporate Governance has a significant positive effect on Stock Performance using the ratio of stock returns and also Price to Earnings Ratio (PER). Keywords: Good Corporate Governance, Return on Assets (ROA), Return on equity (ROE), Net Interest Margin (NIM), Price To Earnings Ratio (PER) and Stock Return.